2023
DOI: 10.1039/d3va00018d
|View full text |Cite
|
Sign up to set email alerts
|

A medical waste X-ray film based triboelectric nanogenerator for self-powered devices, sensors, and smart buildings

Abstract: The rise of plastic waste on the earth and its associated environmental pollution is a major concern for humankind. The reuse of plastic waste for energy harvesting not only reduces...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The latest development in the reuse of plastic waste is using triboelectric nanogenerator (TENG) technology to produce electrical energy. Figure illustrates the TENGs constructed from different waste materials, including household, biowaste, automotive rubber, medical waste, electronic waste, and other waste . However, medical waste has not been extensively explored in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest development in the reuse of plastic waste is using triboelectric nanogenerator (TENG) technology to produce electrical energy. Figure illustrates the TENGs constructed from different waste materials, including household, biowaste, automotive rubber, medical waste, electronic waste, and other waste . However, medical waste has not been extensively explored in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, medical waste has not been extensively explored in the literature. A recent study by our research group has reported a medical waste X-ray sheet-based TENG with a power density of 1.39 W/m 2 . In the present study, we investigated using another type of medical waste, saline bottle (SB) sheets, for energy harvesting, health monitoring, and sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is always a perceptual effort to develop green and sustainable energy sources that can tackle the increasing energy crisis and disposal issues. In 2012, Wang et al proposed the idea of a triboelectric nanogenerators (TENGs) that can effectively convert mechanical energy to electrical energy and emerged as a game-changing invention in the realm of sustainable energy harvesting technology owing to its high energy conversion efficiency, a broad selection of materials, easy device fabrication, and so on. These TENGs have the potential to complement existing renewable energy sources by capturing energy from underutilized sources such as wind, ocean, human motion, rain energy, and acoustic energy to electrical energy and thus can be used to power up nano and microscale electronic devices. Additionally, TENGs have been employed to harness energy from various unconventional sources, including wind and tidal energy. , Some reports even highlight the use of TENGs for capturing energy from rainwater drops . Furthermore, certain nanogenerators have been integrated into hybrid energy systems alongside solar cells .…”
Section: Introductionmentioning
confidence: 99%
“…TENGs convert mechanical vibration into electrical energy based on triboelectrification and electrostatic induction, generating alternating current (AC) signals through repeated contact and separation of materials under the mechanical stimulus. One advantage of TENGs is that they can work with readily available mechanical energy, which is present everywhere. The majority of mechanical signals from the human body use to communicate, such as sound, body movements, and muscle contractions, could also be used in sensors or health monitoring devices with sensitive TENGs. Therefore, TENGs have been considered to be one of the most successful methods for extracting low-frequency mechanical energy for sensor development. By wearing a TENG device on the body respirator, cardiovascular and physical activity can be monitored.…”
Section: Introductionmentioning
confidence: 99%